Family‐based interventions to increase physical activity in children: a systematic review, meta‐analysis and realist synthesis - Brown, H; Atkin, A; Panter, J; Wong, G; Chinapaw, M; van Sluijs, E (Wiley, 2016)
Objective Family‐based interventions represent a potentially valuable route to increasing child physical activity (PA) in children. A dual meta‐analysis and realist synthesis approach examined existing interventions to assist those developing programmes to encourage uptake and maintenance of PA in children. Design Studies were screened for inclusion based on including participants aged 5–12 years, having a substantive aim of increasing PA by engaging the family and reporting on PA outcome. Duplicate data extraction and quality assessment were conducted. Meta‐analysis was conducted in STATA. Realist synthesis included theory development and evidence mapping. Results Forty‐seven studies were included, of which three received a ‘strong’ quality rating, 21 ‘moderate’ and 23 ‘weak’. The meta‐analysis (19 studies) demonstrated a significant small effect in favour of the experimental group (standardized mean difference: 0.41; 95%CI 0.15–0.67). Sensitivity analysis, removing one outlier, reduced this to 0.29 (95%CI 0.14–0.45). Realist synthesis (28 studies) provided insight into intervention context (particularly, family constraints, ethnicity and parental motivation), and strategies to change PA (notably, goal‐setting and reinforcement combined). Conclusion This review provides key recommendations to inform policy makers and other practitioners in developing evidence‐based interventions aimed at engaging the family to increase PA in children, and identifies avenues for future research.